Moi malen'kii fiurer . Moi malen'kii fiurer . My Little Fuhrer . Мой маленький фюрер - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A documentary about Alexandr Shishkin, Hitler's double. Featured in the program: Shishkin, Aleksandr (Actor) Contributors: Senderov, Dmitrii (Anchor) Документальный фильм об Александре Шишкине, двойнике Гитлера. В программе участвуют: Шишкин, Александр (Актер) Создатели: Сендеров, Дмитрий (Ведущий/Ведущая)